2019
DOI: 10.2139/ssrn.3446677
|View full text |Cite
|
Sign up to set email alerts
|

euandi2019: Project Description and Datasets Documentation

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research on the major issues facing the process of European integration, European societies and Europe's place in 21 st century global politics.. The Centre is home to a large post-doctoral programme and hosts major research programmes, projects and data sets, in addition to a range of working groups and ad hoc initiatives. The research agenda is or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Factor analyses conducted after the data collection waves have confirmed the described three-dimensional structure of the data. The a priori decisions regarding which statement should be assigned to which dimension have, in most cases, proven to be valid (Garzia et al, 2015;Michel et al, 2019;Reiljan et al, 2019a).…”
Section: Using Vaas To Place Parties In the Policy Space: The Euandi ...mentioning
confidence: 99%
“…Factor analyses conducted after the data collection waves have confirmed the described three-dimensional structure of the data. The a priori decisions regarding which statement should be assigned to which dimension have, in most cases, proven to be valid (Garzia et al, 2015;Michel et al, 2019;Reiljan et al, 2019a).…”
Section: Using Vaas To Place Parties In the Policy Space: The Euandi ...mentioning
confidence: 99%
“…Nevertheless, it is interesting to note that the total variance explained has increased substantially for CEE countries between the 2009 (74.8) and the 2019 edition (99.8), now surpassing Southern Europe. Although the number and the nature of the factors diverge depending on the election year and/or the region, they generally correspond to the four categories identified in Michel et al (2019). However, in all election years studied, nearly 80% of the variance is accounted for by a three-factor solution tapping on the socioeconomic leftright, pro/anti-EU integration, and a progressive-conservative continuum, as suggested by Garzia et al (2015).…”
Section: Mapping the European Political Space: Validity Of Party Plac...mentioning
confidence: 79%
“…European voters could access euandi again in 2019. The application was developed by the EUI in close collaboration with the University of Lucerne (Switzerland) and reached over 1.2 million users (Michel et al 2019).…”
Section: The History Of Vaas and The Eu Profiler/euandimentioning
confidence: 99%
“…By means of factor analysis, one could measure the extent to which EU foreign policy and security issues load onto the same factor. Analyses of VAA-generated data found that EU-related issues load onto the same factor, while immigration loads onto a distinct factor together with related items such as the acceptance of country's values and expansion of welfare to immigrants (Michel et al 2019). These results could also be put in relationship with voter opinions to compare whether dimensionality in individual-level data matches the one stemming from party-level data.…”
Section: Discussionmentioning
confidence: 96%